2006
DOI: 10.1021/ja0606935
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Ion-Conductive Polymer Films:  Alignment and Fixation of Ionic Channels Formed by Self-Organization of Polymerizable Columnar Liquid Crystals

Abstract: We have prepared two types of one-dimensional ion-conductive polymer films containing ion nanochannels that are both perpendicular and parallel to the film surface. These films have been obtained by photopolymerization of aligned columnar liquid crystals of a fan-shaped imidazolium salt having acrylate groups at the periphery. In the columnar structure, the ionic part self-assembles into the inner part of the column. The column is oriented macroscopically in two directions by different methods: orientation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
327
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(334 citation statements)
references
References 68 publications
2
327
0
5
Order By: Relevance
“…3,4 Even a small quantity of chiral ionic sources can efficiently induce enantiomeric structures in a bulk sample, and ionic moieties can be assembled to form regularly ordered structures. 5,6 These well-ordered ionic moieties are expected to work as efficient cation carriers and scaffolds for ordering cations. These materials, which comprise closely assembled ionic species, can exhibit interesting optical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Even a small quantity of chiral ionic sources can efficiently induce enantiomeric structures in a bulk sample, and ionic moieties can be assembled to form regularly ordered structures. 5,6 These well-ordered ionic moieties are expected to work as efficient cation carriers and scaffolds for ordering cations. These materials, which comprise closely assembled ionic species, can exhibit interesting optical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Carmichael et al 9 have synthesized and explored silicon wafer-assisted SILP materials. They created layers with thicknesses between 10 and 21 nm of an ionic LC with [C 18 6 ] on the planar wafer surface and found that the ionic LC formed a mesophase. Inspired by their work, Wasserscheid et al 7 fabricated SILP materials using silicon nanoparticles and used them as supports for preparing mesoporous structures that could act as effective gasphase catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The increase in molecular weight and the presence of charges often cause an increase in the melting temperature. We have recently reported a polyhedral oligomeric silsesquioxane (POSS)-based room temperature IL that displays a melting temperature below 25 1C.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 31 forms a Col h phase from 20 to 50°C. 48 Without special treatment, these columnar liquid crystals form a polydomain state. The creation of monodomain states with vertical and parallel alignment can be induced by chemical modification of the substrate of the surface and mechanical shearing, respectively.…”
Section: Functional Lc Polymers and Networkmentioning
confidence: 99%
“…45 Highly cross-linked side-chain-type polymers [45][46][47] and network polymerizable functional molecules 48,49 have been prepared to develop free-standing and mechanically tough functional polymers.…”
Section: Introductionmentioning
confidence: 99%